(untitled) (Світ фінансів, 2019)
Ріппа М. Б. Імперативи бюджетного фінансування соціального захисту та соціального забезпечення в Україні. Досліджено теоретичні засади соціального захисту та джерела його фінансового забезпечення. Проведено комплексний аналіз сучасних тенденцій бюджетного фінансування видатків на соціальний захист і соціальне забезпечення населення України за рахунок коштів державного і місцевих бюджетів упродовж 2007–2017 рр., визначено їх частку у ВВП. Проведена порівняльна оцінка темпів зростання бюджетних видатків на соціальний захист, як видатків на споживання з темпами зростання ВВП. Розглянуто пріоритетні напрями бюджетного фінансування соціального захисту та соціального забезпечення. Визначено основні проблеми та особливості бюджетного фінансування соціального захисту та запропоновано заходи щодо його модернізації. Риппа М. Б. Императивы бюджетного финансирования социальной защиты и социального обеспечения в Украине. Исследованы теоретические основы социальной защиты и источников ее финансового обеспечения. Проведен комплексный анализ современных тенденций бюджетного финансирования расходов на социальную защиту и социальное обеспечение населения Украины за счет средств государственного и местных бюджетов в течении 2007–2017 гг. Определены их доли в ВВП. Проведена сравнительная оценка темпов роста бюджетных расходов на социальную защиту, как расходов на потребление с темпами роста ВВП. Рассмотрены приоритетные направления бюджетного финансирования социальной защиты и социального обеспечения. Определены основные проблемы и особенности бюджетного финансирования социальной защиты и предложены меры по его модернизации. Rippa M. Imperatives of budgetary financing of social protection and social security in Ukraine. Introduction. The state of financial provision of social protection at the expense of budgetary funds is an important issue for each state. Purpose. The purpose of the article is to scientifically substantiate the theoretical foundations of social protection of the population and the sources of its financial support. Results. Expenditures on social protection of the population occupy a significant place in the state expenditures of Ukraine. Through the system of social protection during 2010–2016, about 23% of GDP was allocated. A tendency towards a decrease in their share (in 2016 – 18,2%) was revealed. Budget financing takes the lead in the system of sources of financial support. Due to the budget system, 10.8% is distributed, while in the structure of total expenditures of the Consolidated Budget expenditures on social protection and social security make up 59,6%. A comprehensive analysis of the dynamics of volumes and structure of budget financing during 2007–2017 was conducted. A tendency towards annual growth of expenditures on social protection has been established, and it has been found that their growth rates during the investigated period significantly exceeded GDP growth rates. A significant level of centralization is established. Such a situation requires the optimization of budgetary expenditures on social security and social security and the modernization of sources of their financial support. Conclusions. The main vectors for improving the budget financing of social protection and social security in Ukraine are: – decentralization of budget financing of social protection and social security; – provision of social transfers based on the verification of the property and financial status of the recipients; – the targeted nature of social assistance; – monetization of subsidies; – optimization of the state policy in the labor market with a view to its rapid adaptation to structural changes taking place in the economy; since socially-market economy is aimed not only at social protection, but also the creation of such an organizational and economic mechanism that would contribute to reducing the part of the population that needs state paternalistic care (social assistance).